Dinamika Pendidikan Karakter Siswa di SMP Negeri 2 Sungai Pua Kabupaten Agam - Sintia S; Januar J (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The aim of this research is to determine 1) the dynamics of character education in Islamic religious education learning at SMP Negeri 02 Sungai Pua, Agam Regency. 2) Supporting and inhibiting factors for character education in learning Islamic religious education in class VII SMP Negeri 2 Sungai Pua, Agam Regency. The method used in this research is descriptive qualitative field research. The key informants in this research were PAI teachers, while the supporting informants were the school principal, class teacher and students of SMP Negeri 2 Sungai Pua. The results of the research show that a) The dynamics of character education in Islamic religious education learning at SMP Negeri 2 Sungai Pua, namely integrated character education through learning, has been carried out well, but there are still some students who are less prepared for the learning process and are not active in the process. integrated character education through school management has been well planned in its planning, but when implemented in schools, it still faces obstacles such as limited educational staff and limited time and integrated character education through student activities has been implemented effectively, although there are still some students who lack have awareness in participating in these activities. b) Supporting factors for implementing character education include the presence of direction from the teacher, the existence of facilities and infrastructure, providing opportunities for students to practice cults every Friday, midday prayers in congregation, getting used to giving alms, giving time to learn tahfiz, getting used to speaking politely, support from parents and strict rules from the school. Meanwhile, inhibiting factors include lack of time allocation, the outside environment where they play, cellphones which can have a bad impact and there are still students who are still lazy.